+0

0
203
6  Ignore the one that is crossed out. I already completed that one but then I got stuck on the others. Please show work. Thank you.

Feb 11, 2019

#1
+1

Can you post this as latex instead?

Feb 11, 2019
edited by JohnyGotchaApples  Feb 11, 2019
#2
0

How do I post it as latex??

Guest Feb 11, 2019
#3
+1

$$\left(2a^2b=5b^3+4a^4b^2\right)-\left(7b^3+8a^4b^2-7a^2b\right)$$

simplify

$$\left(2\cdot \:5=a^2b^3b+4a^4b^2\right)-\left(7b^3+8a^4b^2-7a^2b\right)$$

simplify

$$\left(2a^2b=5b^3+4a^4b^2\right)-7b^3-8a^4b^2+7a^2b$$

.
Feb 11, 2019
#4
+1

$$(2a^2b-5b^3+4a^4b^2)-(7b^3+8a^4b^2-7a^2b)\\ =(2a^2b-5b^3+4a^4b^2)-7b^3-8a^4b^2+7a^2b\\ =(4a^4b^2-8a^4b^2)+(-5b^3-7b^3)+(2a^2b+7a^2b)\\ =-4a^4b^2-12b^3+9a^2b$$

.
Feb 14, 2019
#5
+1

$$(1-2n)^3 - 7n(n^2-2)\\ = (1-2n)(1-2n)^2 -7n^3+14n\\ =(1-2n)(1-4n+n^2)-7n^3+14n\\ =(1-4n+n^2)-2n(1-4n+n^2)-7n^3+14n\\ =1-4n+n^2-2n+8n^2-2n^3-7n^3+14n\\ =1+(-4n-2n+14n)+(n^2+8n^2) + (-2n^3-7n^3)\\ =-9n^3+9n^2+8n+1$$

.
Feb 14, 2019
edited by MaxWong  Feb 14, 2019
#6
+1

$$4(2-3w)(w^2-2w+10)\\ =(8-12w)(w^2-2w+10)\\ =8(w^2-2w+10) - 12w(w^2-2w+10)\\ =8w^2-16w+80-12w^3+24w^2-120w\\ =-12w^3+32w^2-136w+80$$

.
Feb 14, 2019